Media Interaktif Bahasa Jawa untuk Meningkatkan Literasi Bahasa Daerah Anak Usia Dini - Nurul Fauziah; Erni Munastiwi (Universitas Islam Tribakti Lirboyo Kediri, 2025)
The decline in the use of Javanese in the environment has made educators aware of the importance of media innovation to improve regional language literacy. This is a form of institutional support to preserve regional languages, because regional languages ​​need to be introduced to the next generation from an early age. The purpose of this study is to develop a Javanese language media to facilitate educators in introducing regional literacy to children. The research subjects were 15 children and was conducted at Masyithoh II Sanansari Kindergarten. This study used a development model or Research and Development (R&D) in the form of ADDIE which went through five stages: 1) Analysis; 2) Design; 3) Development; 4) Implementation; 5) Evaluation. The results of the study were in the form of the development of Javanese language media called